Strategi Komunikasi Pemasaran Menggunakan Media Luar Ruang Pada CV A&A Real Estate Sebagai Keputusan Pembeli - Wijaya, I Gede Oka Rastra; Kristiyono, Jokhanan (LPPM Stikosa-AWS, 2024)
The background to this research will focus on discussing marketing communication strategies using outdoor media in the development of the digital era, especially in property marketing communication strategies using outdoor media as promotional media. In this digital era, many people use social media to market the products or goods they want to sell, but CV. A&A real estate continues to use billboards which are still considered more effective than social media, CV. A&A real estate also uses social media to market the properties it owns but is considered less effective. CV. A&A Real Estate uses outdoor media promotions as an effective strategy to increase visibility and reach a wider market. outdoor media that is large, attracts attention, and is placed in strategic locations that are busy with traffic or visited by many people. This promotional media offers the advantage of conveying information about the property visually and strikingly. The use of outdoor media provides many benefits for CVs. A&A Real Estate, especially in the context of a property market where the majority of potential buyers are adults, who may not be too fixated on the use of social media. In this case, outdoor media is a more suitable medium because it can reach a different and wider target audience. This research will discuss the implementation of marketing communication strategies using outdoor media used by CV.A&A real estate so that it can provide benefits or solve problems in building and competing for real estate in the digital era.